Levonorgestrel-releasing intrauterine device versus oral progesterone for treatment of simple endometrial hyperplasia without atypia - Hatice Kansu-Celik; Burcu Kisa Karakaya; Ozlem Evliyaoglu; Yaprak Engin-Ustun (Medicine Science, 2018)
The aim of this study was to compare the efficacy and effect on the menstrual pattern of the levonorgestrel releasing intrauterine device versus oral progesterone for treatment in patient having simple endometrial hyperplasia (EH) without atypia. Patients who underwent endometrial sampling with abnormal uterine bleeding history and received simple EH without atypia were included in this study between 1 December 2015 and 31 March 2016, retrospectively. Twenty-two patients were treated with the levonorgestrel-releasing intrauterine device (LNG-IUD) and 47 with oral progesterone. Primary outcome measures were regression of hyperplasia after 3 months of therapy. Secondary outcome measures were effect on menstruel pattern during treatment, or rates of hysterectomy and recurrence within a 12 month period. After 3 months of treatment, regression of EH occurred in all of women in LNG-IUD group versus 93% of women in the oral progesterone group (p=0.226). Hb values were increased at the 3th month measurement in both of groups. Endometrial thickness was significantly decreased at the end of the 3th month (p< 0.001). Amenorrhea was more common in the LNG-IUD group (p [Med-Science 2018; 7(1.000): 21-24]